VARIASI KELUASAN MAKNA TEKSTUAL DALAM TEKS DWIBAHASA FIVE ON THE TREASURE DAN LIMA SEKAWAN DI PULAU HARTA - Devi Rosmawati (Adabiyyāt: Jurnal Bahasa dan Sastra, 2013)
The study aims to describe the variation of textual meaning breadth (VTMB) on Five on the Treasure Island and Lima Sekawan di Pulau Harta, to describe the meaning of VTMB in translational context, and to interpret the contextual factors that cause VTMB. This is descriptive-qualitative research. The data sources are two novels. This research focuses on the clauses unit. The instrument is the researcher herself by applying the concept of Translational Semiotic Communications (TSC) and the Halliday’s concept of textual meaning. The validity testing is done through triangulation. The results of this research indicate that the dominant variation of T1 and T2 is very low (T1=T2). It is supported by the highest figure of the zero variation which is 552 or 63, 52%, the most prominent mean of two texts which is on T1. It can be seen from score 193 or 22, 21%. There are kinds of themes that motivate the TMB. They are interpersonal theme, topical theme, and textual theme. Contextual factor, that motivates the textual meaning breadth of the two texts, are situational context and cultural context. In short, situational context consist of field, tenor and mode. Cultural context can be seen from the cultural terms in T1 used in T2. The title in T2 is the same as T1. This indicates that T2 intertextualizes with T1.